Model konseptual IMTA dan RIMTA pada budidaya lobster di karamba jaring apung (KJA) - Rokhmad Mohamad Rofiq; Muhammad Rifqi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2021)
In order to optimize the economic value of tropical lobster resources in Indonesian waters, it is important to immediately develop lobster culture, both of domestic farmers and businesses. Based on existing adoption of tropical lobster culture technology, the business segment on tropical lobster culture can be divided into two types, those are rearing stages should be implemented at the technical implementation unit (UPT) facilities of the Directorate General of Aquaculture Fisheries, while the next stages is the grow up of lobsters in the floating net cages can involve the local coastal community or farmers and businesses. Integrated Multi Tropic Aquaculture (IMTA) implementation on lobster cultivation both on unit and regional scale can realize the principle of sustainability, optimize resource utilization, increase the acceptance of farmers and community involvement, provide environmental services of extractive commodities and at the same time as the contribution of aquaculture fisheries in the mitigation of greenhouse gas emissions. Some extractive commodities that are potentially cultured with lobster are seaweed, shellfish, sea cucumbers and some types of low-level tropical fish. It takes research related to effective feed for seed and grow up and its management, optimal environmental parameters, cultivation methods, types of pests and diseases of lobsters and their treatment.